Pelayanan Khusus Bagi Narapidana Perempuan Terhadap Pemenuhan Hak Kesehatan Reproduksi Di Lapas Kelas IIB Cilacap - Inggar Rinukti (Widya Yuridika, 2021)
Women are special creatures created by God as ihsan who deserve to be loved and respected. Women were created by Allah SWT with the privilege of obtaining beauty and sophistication from the reproductive system. That the reproductive system is used as a tool to create offspring or new generations for mankind. On this basis, women are entitled to reproductive health services including female prisoners. Correctional institutions in Indonesia adhere to the correctional system, which is that the conceptual and historical system is very different from the prison system. The prison system is motivated by the concept of fostering and guiding it is very different from the prison system which is motivated by the concept of retaliation. Reflection on the concept of developing WBP (Correctional Assistance Residents) is based on the "10 principles of correctionalism" written in the Ministry of Justice No. M.02-PK.04.10 in 1990. Female prisoners pose separate barriers to prison officers for those who are part of a very small group in the prison community. The percentage of access to female prisoners to get health and care services is smaller than that of male prisoners. Services for reproductive health are limited or even non-existent and materials regarding health promotion, information and treatment are limited. The aim of the research is to find out the special services for female prisoners to fulfill the reproductive health rights in Lapas Kelas IIB Cilacap.